The Whaling Season - Mull Charles (Island Press, 2003)
Science and environmental writer Mulvaney offers a passionate, stirring account of his involvement in Greenpeace's campaign to end commercial whaling, taking readers through the history of whaling and of the environmental organization itself (which was founded in 1971), and offering an explanation of what's being done to nonviolently stop whalers' lethal practices. Mulvaney has participated in numerous Greenpeace-led expeditions to the waters surrounding Antarctica in an effort to intercept whalers and stop them from killing endangered whales. It's an inspiring story, told honestly and in a non-preachy style. After many frustrations, Mulvaney finally comes to realize that "at the heart of the conflict there is, I suspect, a fundamental cultural dichotomy... a profound contrast in beliefs over how humanity should relate to the natural environment." His important book deserves attention from anyone who cares about the fate of the ocean's greatest creatures.